2014
DOI: 10.1039/c3ay42227e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of selenium in soil samples using high-resolution continuum source graphite furnace atomic absorption spectrometry and direct solid sample analysis

Abstract: Least squares background correction (LSBC) for spectral interference of the NO and PO molecules in the determination of Se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Schiller et al 154 reported a four-step column chromatographic procedure of Cr isolation prior to measurement. Results indicated that reproducibility was better than 54 Cr AE5.8 Â 10 À6 although more sample was required than during traditional TIMS analysis. The largest 52 Cr signal was monitored using a 10 10 U resistor to allow >50 V beam intensities, while a 10 12 U variant was used for the small 49 Ti and 56 Fe signals.…”
Section: Stable Isotope Systematicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Schiller et al 154 reported a four-step column chromatographic procedure of Cr isolation prior to measurement. Results indicated that reproducibility was better than 54 Cr AE5.8 Â 10 À6 although more sample was required than during traditional TIMS analysis. The largest 52 Cr signal was monitored using a 10 10 U resistor to allow >50 V beam intensities, while a 10 12 U variant was used for the small 49 Ti and 56 Fe signals.…”
Section: Stable Isotope Systematicsmentioning
confidence: 97%
“…Successful determination of F in plant materials, 53 Se in soils 54 and S in coal and y ash 55 were described. Direct analysis of solid samples using HR-CS-GF MAS has been reported by several groups of workers.…”
Section: Solidsmentioning
confidence: 99%
“…143 Solid-sampling fl ame AAS (HR-CS-F AAS) has a number of limitations associated with the sensitivity of determination and interference. Therefore, atomic absorption analysis of solid samples can be best done using HR-CS graphite furnace atomic absorption spectrometry (HR-CS-GF AAS) (see Refs 19,22,23,[27][28][29][43][44][45][47][48][49]58,70,73,76,77,89,101,102,108,116,126,131,132).…”
Section: Solid-sampling High-resolution Continuum Source Graphite Furnace Atomic Absorption Spectrometry (Hr-cs-gf Aas)mentioning
confidence: 99%
“…Indeed, the SS HR-CS GFAAS has the possibility of monitoring multiple lines, improving background correction based on least-squares algorithm and integrating automatic solid sampler and microbalance, which may reduce errors caused by manual operations [10]. The SS HR-CS GFAAS has been applied in soil analysis for determination of Cd and Fe [11,12], Cd, Cr, Fe, Al [13], Se [14], Sb [15], Ag [16]. However, the literature is lacking in reports concerning the determination of Co, V, Mo and Ni in soil by SS HR-CS GFAAS.…”
Section: Introductionmentioning
confidence: 99%